Immigrant narratives in German newspapers - Kai Gehring; Joop Adema; Panu Poutvaara (EconPol Forum, 2023)
We measure immigrant narratives in German newspapers and assign each sentence to one of seven themes. Using natural language processing (NLP) tools and customized dictionaries, we analyze over 100,000 articles. 45 percent of narratives are on Foreign Religion, 23 percent on Cultural Integration, and only 12 percent on Economic themes. Changes in sentiment in immigrant narratives come mainly from shifts between themes. Southern and Eastern European immigrants receive much more positive coverage than Arabs and Turks
Keywords: 330